Does firm size matter for the financial constraints? - Ismail , Mohd Adib; Ibrahim, Mansor; Yusoff, Mohammed; Zainal, Mohd-Pisal (Penerbit Universiti Kebangsaan Malaysia, 2010)

(untitled)
This article empirically investigates the presence of financial constraints in the Malaysian capital market. The existence of financial constraints gives firm less access to external funds to finance their investment activities. Therefore, the constrained firm has to rely on internal sources of financing. The severity of financial constraints is relatively different according to firm size. Hence, the sample is divided into large and small firm subsamples. Using the Q model of investment, the results show that financial constraints are present in the Malaysian market using the full sample. The subsample results however show that large firms are not financially constrained. On the other hand, the smaller firms are facing the constraints in their investment decisions.